A 12-month longitudinal naturalistic follow-up of cariprazine in schizophrenia - Carmassi, Claudia; Dell’Oste, Valerio; Fantasia, Sara; Bordacchini, Andrea; Bertelloni, Carlo Antonio; Scarpellini, Pietro; Pedrinelli, Virginia (Frontiers in Psychiatry, 2024)
Background: Cariprazine, a third-generation antipsychotic (TGAs), has demonstrated efficacy in the treatment of schizophrenia with good tolerability profile. Actual real-world literature data are lacking, particularly when exploring its efficacy in the long term. The present study examined the effects of cariprazine treatment on specific psychopathological domains with a particular focus on outcomes and side effects in real-life experience, after a long-term treatment. Methods: The present 12-month longitudinal naturalistic study included a sample of subjects with a DSM-5-TR diagnosis of schizophrenia, recruited in the outpatients' psychiatric services of university and community hospitals in Italy, naturally treated with cariprazine. The assessments included: a sociodemographic data sheet, the Structured Clinical Interview for the DSM-5 (SCID-5), the Positive and Negative Symptom Scale (PANSS) and the St. Hans Rating Scale (SHRS). The PANSS was also administered after 6 (T1) and 12 (T2) months of treatment with cariprazine while the SHRS at T1. Results: The total sample consisted of 31 patients, 15 males and 16 females. A significant decrease of the PANSS' subscales, Marder factors and total mean scores emerged at both T1 and T2 with respect to T0. Extrapyramidal symptoms occurred in a minority of patients and in mild or mild/moderate forms: no patient showed moderate forms of psychic/motor akathisia or dystonia, three subjects showed moderate parkinsonism.This study confirms a good efficacy profile of cariprazine in both positive and negative symptoms in patients with Schizophrenia, combined with a good tolerability profile in extrapyramidal symptoms.